The Impact of Quillbot Tools on Critical Thinking Skills Among University Students in Tanzania - Marco Edward; Noel Julius Ntawigaya (Indonesian Educational Research Journal, 2025)
This paper investigates the impact of QuillBot on critical thinking among university students at Teofilo Kisanji University (TEKU), Tanzania. The study employed a qualitative research approach within the interpretivist paradigm. Data were collected through semi-structured open-ended interviews and documentary analysis. Content analysis was used to analyze the data and identify key themes. A sample of fifteen participants, including lecturers, university administrators, and students, was selected for the study. The findings indicate that QuillBot has both positive and negative effects on critical thinking among university students. The negative impacts include overdependence on technology, reduced original thought, academic integrity concerns, decreased discussion and debate, potential plagiarism, while the positive impacts include enhanced language proficiency, increased research efficiency, improved self-confidence, learning, and writing skills. The study found that while QuillBot, as an artificial intelligence tool, has supported the development of critical thinking, some students have become overly reliant on it, neglecting to engage their own thinking effectively. It is recommended that the government, through media outlets, provide education on the benefits and drawbacks of using QuillBot in teaching and learning